Inside Bank Lending: Financial Ratios and Monetary Variables - Sabry, Mayra; Maski, Ghozali (Contemporary Studies in Economic, Finance and Banking, 2026)
This study examines the effects of internal banking factors and monetary variables on credit distribution of conventional commercial banks in Indonesia during 2018-2025. Internal factors include CAR, CKPN, COF, DPK, and LAR while monetary variables consist of inflation and the BI7DRR. Monthly time-series data from OJK and Bank Indonesia are analyzed using the Engle-Granger Error Correction Model (ECM) to capture short-run dynamics and long-run relationships. The results show that in the short run, CAR and CKPN negatively affect credit, while DPK has a positive and significant effect. In the long run, DPK, inflation, and BI7DRR significantly influence credit distribution, whereas other variables exhibit no consistent impact. These findings suggest that credit dynamics are shaped by both internal banking conditions and long-term monetary transmission mechanisms.